A Prospective Observational Study of Technical Difficulty With GlideScope-Guided Tracheal Intubation in Children. (August 2018) - Zhang, Bin; Gurnaney, Harshad G.; Stricker, Paul A.; Galvez, Jorge A.; Isserman, Rebecca S.; Fiadjoe, John E.
Abstract : BACKGROUND: The GlideScope Cobalt is one of the most commonly used videolaryngoscopes in pediatric anesthesia. Although visualization of the airway may be superior to direct laryngoscopy, users need to learn a new indirect way to insert the tracheal tube. Learning this indirect approach requires focused practice and instruction. Identifying the specific points during tube placement, during which clinicians struggle, would help with targeted education. We conducted this prospective observational study to determine the incidence and location of technical difficulties using the GlideScope, the success rates of various corrective maneuvers used, and the impact of technical difficulty on success rate. METHODS: We conducted this observational study at our quaternary pediatric hospital between February 2014 and August 2014. We observed 200 GlideScope-guided intubations and documented key intubation–related outcomes. Inclusion criteria for patients were <6 years of age and elective surgery requiring endotracheal intubation. We documented the number of advancement maneuvers required to intubate the trachea, the location where technical difficulty occurred, the types of maneuvers used to address difficulties, and the tracheal intubation success rate. We used a bias-corrected bootstrapping method with 300 replicates to determine the 95% confidence interval (CI) around the rate of difficulty with an intubation attempt. RESULTS: After excluding attempts by inexperienced clinicians, there were 225 attempts in 187 patients, 58% (131 of 225; bootstrap CI, 51.6%–64.6%]) of the attempts had technical difficulties. Technical difficulty was most likely to occur when inserting the tracheal tube between the plane of the arytenoid cartilages to just beyond the vocal cords: "zone 3." Clockwise rotation of the tube was the most common successful corrective maneuver in zone 3. The overall tracheal intubation success rate was 98% (CI, 95%–99%); however, the first attempt success rate was only 80% (CI, 74%–86%). Patients with technical difficulty had more attempts (median [interquartile range], 2 [1–3] than those without technical difficulty median (interquartile range, 1 [1–1; P value <.01]). CONCLUSIONS: A variety of clinicians experience technical difficulties with the GlideScope Cobalt videolaryngoscope in children. These difficulties result in more tracheal intubation attempts, an important risk factor for intubation-associated complications. Targeted education of clinicians may reduce the incidence of technical difficulties.